Implementation of Law Number 2 of 2012 Concerning Land Acquisition For Public Interests in The City Of Palopo - Jamal Qadar J.; Syamsiar Syamsiar; Ridwan Pakambanan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study to analyze the implementation of Law Number 2 of 2012 concerning Land Acquisition for Public Interest in Palopo City and to identify the supporting and inhibiting factors affecting its implementation. The study was motivated by several challenges in land acquisition practices, including inconsistencies in land administration data, limited human resources, low public understanding of land acquisition procedures, and objections regarding compensation mechanisms. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation studies. The informants consisted of the Head of the Palopo City Land Office, the Head of Land Services Division, the Land Acquisition Implementation Team, representatives of the National Land Agency (BPN), and community members affected by land acquisition. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The analysis was guided by George C. Edwards III’s policy implementation theory, consisting of communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of Law Number 2 of 2012 in Palopo City has generally been carried out effectively. In terms of communication, socialization and public consultations have been conducted, although public understanding of compensation mechanisms still requires improvement. Regarding resources, the availability of personnel, facilities, and land administration data has supported policy implementation, despite limitations in staffing and land administration issues. In terms of disposition, government officials demonstrated commitment, professionalism, and transparency in service delivery. Regarding bureaucratic structure, land acquisition activities have been implemented according to established procedures and supported by inter-agency coordination. Supporting factors include a clear legal framework, inter-agency coordination, local government support, information transparency, and the commitment of implementing officials. Meanwhile, inhibiting factors include limited human resources, inadequate land administration records, inconsistencies in land data, low public understanding, and lengthy administrative procedures.